ANALISIS KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK KELAS VIII MTsN 6 KOTA PADANG - Refni Defita (Jurnal Edukasi dan Penelitian Matematika, 2023)
The capacity to solve problems is a skill that must be cultivated in order to study mathematics. Students in grade VIII MTsN 6 Padang City, however, have not fully grasped this capacity for problem solving. This study intends to describe the aptitude for mathematical problem-solving of MTsN 6 Kota Padang pupils in class VIII. Descriptive study utilizing a qualitative approach is a technique used. The outcomes demonstrated that pupils at MTsN 6 Kota Padang have a respectable aptitude for problem-solving. In the high group, they could comprehend the issue, proficient in creating and enacting action plans, and less able to reflect on the past. The medium group had a clear comprehension of the issue, but they struggled to come up with ideas, put them into action, and assess their effectiveness. The bottom group has not met the four criteria for problem solution.Keywords. – problem solving abilities, mathematical